2010
DOI: 10.1007/s10508-010-9678-0
|View full text |Cite
|
Sign up to set email alerts
|

“I Kiss Them Because I Love Them”: The Emergence of Heterosexual Men Kissing in British Institutes of Education

Abstract: In this article, we combined data from 145 interviews and three ethnographic investigations of heterosexual male students in the U.K. from multiple educational settings. Our results indicate that 89 per cent have at some point kissed another male on the lips which they reported as being non-sexual: a means of expressing platonic affection among heterosexual friends. Moreover, 37per cent reported also engaging in sustained same-sex kissing, something they construed as nonsexual and non-homosexual. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 20 publications
3
85
3
Order By: Relevance
“…Drummond et al (2015) examined the prevalence of kissing among straight male athletes and non-athletes in an Australian university. Concurrent with the findings of previous inclusive masculinity scholarship on same-sex kissing 6 (Anderson, Adams and Rivers, 2012), Australian men were also kissing their male friends (Drummond et al 2015), although in lesser rates than British men, and higher rates than American. Although Anderson (2014) found more non-athletes to be kissing than athletes, in the UK, this was not evident in the Australian study.…”
Section: Inclusivitysupporting
confidence: 59%
See 2 more Smart Citations
“…Drummond et al (2015) examined the prevalence of kissing among straight male athletes and non-athletes in an Australian university. Concurrent with the findings of previous inclusive masculinity scholarship on same-sex kissing 6 (Anderson, Adams and Rivers, 2012), Australian men were also kissing their male friends (Drummond et al 2015), although in lesser rates than British men, and higher rates than American. Although Anderson (2014) found more non-athletes to be kissing than athletes, in the UK, this was not evident in the Australian study.…”
Section: Inclusivitysupporting
confidence: 59%
“…Further literature on soccer supports the claim that homophobia is in decline both on the playing field and among spectators Cleland, 2011, 2012;Cleland, 2014;Magrath, Anderson and Roberts, 2013), and thus the positive environments found in both of the above studies (Adams and Anderson, 2012;Anderson, 2011b;Anderson and Adams, 2011) are not as a result of uniquely liberal environments. Athletes are no longer required to be athletically elite, rather regardless of sporting ability homosexual athletes are being embraced by their teammates (Anderson, 2011a).…”
Section: Imt and Sportmentioning
confidence: 66%
See 1 more Smart Citation
“…It has also been found that heterosexual men in Britain (Anderson, Adams and Rivers, 2012), Australia (Drummond, Filiault, Anderson and Jeffries, 2014) and 6 the United States (Anderson, 2014) frequently kiss one another as expressions of homosocial endearment.…”
Section: Inclusive Masculinity Theorymentioning
confidence: 99%
“…The influence of inclusive masculinities on heterosexual men's friendships in university settings has been intensively investigated (Anderson, Adams, & Rivers, 2012), alongside research which has documented markedly improved experiences for bisexual students (Anderson, McCormack, & Ripley, 2014;Morris et al, 2014). Taulke Johnson's (2008) research with gay male undergraduates found more positive experiences of university life than earlier research (Epstein et al, 2003;Rivers & Taulke-Johnson, 2002).…”
Section: From Orthodox To Inclusive Masculinitiesmentioning
confidence: 99%